Testing of Reproducibility and Consistency of Commonly Used Five Different Antioxidant Capacity Methods on Turnip Juice - Metin Konuş; Can Yılmaz; Nizamettin Özdoğan; Doğan Çetin; Nurhan Didem Kızılkan; Abdussamet Kayhan (Turkish Journal of Agriculture: Food Science and Technology)
Antioxidants, usually contain phenolic groups, molecules may prevent the formation of free radicals or by blocking the radicals to prevent damage to the cell. Antioxidant molecules can be produced by the body or taken into the body through foods. Today, there are many different methods used to measure antioxidant capacity. In these methods, measurements are usually carried out by adding the tested substances into a solution containing free radicals. These methods can give different results depending on the characteristics of the reactant used. In this study, the reproducibility and consistency of five different antioxidant capacity methods (DPPH, ABTS, galvinoxil, phosphomolybdenum and FRAP) in commercially available and homemade turnip samples were tested. At the end of the study, antioxidant activities of the tested samples were evaluated. According to the evaluation of the antioxidant activities (from higher to lower) of these samples, the results of, DPPH, galvinoxyl, phosphomolybdenum and FRAP methods were very similar. However, ABTS method results showed difference compared to other method results. As a result of study, reproducibility and consistency of results of DPPH, galvinoxyl, phosphomolybdenum and FRAP methods were determined.